Wybrane ekonomiczno-społeczne efekty prywatyzacji przedsiębiorstw poprzez leasing pracowniczy - Szczepkowska, Malwina (The Employee Leasing in Company's Privatization in Poland, 2005)
Property transformations that have taken place in our country aim at raising the effectiveness of functioning of economic entitles (and in consequence that whole economy). For 10 years of company's privatization in Poland one of the most often applied method is employee leasing. The paper presents staff companies and effects of privatization this form of companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 426-436